Effect of microstructure on fracture toughness on industrial alloys - Wee, Benjamin William Wei Wen. (2011)
This report will cover the steps taken, the tests conducted and the equipments used to investigate the effect of microstructure on fracture toughness on API-5L. This is a widely used pipeline material for the transportation of combustible fluids. In ensuring that the minimal mechanical requirements are met, the properties of the material are evaluated through various mechanical tests.